Does GVC participation improve firm productivity? A study of three developing Asian countries - Shujiro Urata; Youngmin Baek (Asian Development Bank Institute (ADBI), 2021)
This paper examines the impact of local firms' participation in global value chains (GVCs) on productivity by considering three different patterns of GVC participation. We conducted a DID-PSM estimation involving three countries, Indonesia, the Philippines, and Viet Nam, and 17 manufacturing sectors in 2009 and 2015. We found an endogenous relationship between firm productivity and GVC participation: firms that enter GVCs have high productivity before participating in the GVCs (selection effect), and only Indonesian firms which entered GVCs had a high productivity growth after joining GVCs (learning effect). These two effects were only found for firms which both import intermediate goods and export output, and not for firms which only either import or export. We also found that indirect exporting does not improve a local firm's productivity. Several recommendations are made to help firms and governments facilitate the participation of firms in GVCs.
Keywords: D24; F14; L11; 330; global value chains; productivity